Vexing issues of knowledge sharing: The case study of the wiki initiative in a Malaysian public organization - Md Khuzaimah, Khairil Hizar; Hassan, Padzil @ Fadzil; Keoy, Kay Hooi; Othman, Roznita (2012)
While many organizations have benefited from the existence of Internet-based web applications such as wikis and blogs as tools for knowledge sharing , many others have failed. In the end, wikis and blogs are reduced to just as the facilities to provide one-way information about the organization. Gone is the exuberance when the wiki or blog was first launched.Failures of wikis in promoting knowledge sharing are mostly not because their poor design.Many fail because of poor understanding of the ecosystem within which effective wikis operate.To emphasize, this paper presents a case study of a wiki initiative mooted by a public organization to manage and share knowledge.Notwithstanding the many initiatives introduced to encourage active knowledge sharing participation, maintaining a sustainable knowledge sharing culture within the organization can be very complex.The case study provides useful examples of this and lessons that can be learnt.The findings suggest that that the variables surrounding the organization can be unique.It is necessary to endeavor and continuously learn to determine the critical success factors and the ecosystem before successful and sustainable wiki portals for knowledge sharing can effectively be promoted.